Nanotherapeutics for the Treatment of Hepatocellular Carcinoma - Mukherjee, Biswajit (Bentham Science Publishers, 2022)
Hepatocellular carcinoma (HCC) is a leading cause of death globally. Conventional chemotherapeutic agents are unable to penetrate cancerous hepatocytes completely and are toxic to non cancerous cells and tissues. This toxicity significantly compromises the therapeutic outcome of conventional chemotherapeutic agents which is also reflected in the high mortality of the disease. Nanotherapeutics have shed new light onto HCC treatment by enabling site-specific in vivo delivery of chemotherapeutics specifically to neoplastic hepatocytes without affecting normal hepatocytes. Thus, nanotherapeutics h.